Phocaiecola vulgatus Bacteraemia: The Chicken-and-Egg in Colorectal Carcinoma - Nurnabilah, Zainuddin; Nur Zulieffa, Zakaria; Alisa Hanum, Arba’eni @ Arbaen; Habib, Abdul Hakim Esa; Norashikin, Samsudin (2025)
Phocaeicola vulgatus, formerly known as Bacteroides vulgatus, is a Gram-negative anaerobic bacterium, exclusively inhabiting the human colon.